Overexpression, purification and characterisation of homologous α-l-arabinofuranosidase and endo-1, 4-β-d-glucanase in Aspergillus vadensis. (1st November 2014) - Culleton, Helena; McKie, Vincent A; de Vries, Ronald P
Abstract: In the recent past, much research has been applied to the development of Aspergillus, most notably A. niger and A. oryzae, as hosts for recombinant protein production. In this study, the potential of another species, Aspergillus vadensis, was examined. The full length gDNA encoding two plant biomass degrading enzymes, i.e. α -l -arabinofuranosidase ( abfB ) (GH54) and endo -1, 4- β -d -glucanase ( eglA ) (GH12) from A. vadensis were successfully expressed using the gpdA promoter from A. vadensis . Both enzymes were produced extracellularly in A. vadensis as soluble proteins and successfully purified by affinity chromatography. The effect of culture conditions on the expression of abfB in A. vadensis was examined and optimised to give a yield of 30 mg/L when grown on a complex carbon source such as wheat bran. Characterization of the purified α -l -arabinofuranosidase from A. vadensis showed an optimum pH and temperature of pH 3.5 and 60 °C which concur with those previously reported for A. niger AbfB. Comparative analysis to A. niger AbfA demonstrated interesting differences in temperate optima, pH stability and substrate specificities. The endo -1, 4- β -d -glucanase from A. vadensis exhibited a pH and temperature optimum of pH 4.5 and 50 °C, respectively. Comparative biochemical analysis to the orthologous EglA from A. niger presented similar pH and substrate specificity profiles. However, significant differences in temperature optima and stability were noted.